Polyurethane foam composition, polyurethane foam, preparation method of polyurethane foam and refrigeration device
By modifying hollow glass microspheres and nano-silica fillers through silane coupling modification, and combining appropriate catalysts and antioxidants, the problems of high thermal conductivity and filler sedimentation in polyurethane foam were solved, and the preparation of low thermal conductivity and high strength polyurethane foam was achieved, which is suitable for high-energy-efficiency refrigerators.
Patent Information
- Application Number
- CN202511785792.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-01-23
AI Technical Summary
Existing polyurethane foam compositions produce polyurethane foams with high thermal conductivity, and traditional foaming processes are not suitable for high-filler systems, which are prone to filler settling and foam rupture, leading to performance fluctuations.
Modified hollow glass microspheres and modified nano-silica were used as fillers. They were modified with silane coupling agents and combined with appropriate amounts of catalysts, stabilizers and antioxidants to react with isocyanates to form polyurethane foam. The foaming and curing processes were controlled to form a polyurethane foam composition with a high filler system.
It effectively reduces the thermal conductivity of polyurethane foam to below 0.017 W/(mK), improves compressive strength and compressive strength stability, ensures uniform cell size, and takes into account both environmental protection and cost control.
Smart Images

Figure CN121378638A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of thermal insulation materials, and particularly relates to a polyurethane foam composition, a polyurethane foam and a preparation method thereof, and a refrigeration device. BACKGROUND
[0002] Polyurethane foam (PU foam for short) is a porous material formed by the polymerization of isocyanate and polyol (and other additives) to form a polyurethane (PU) matrix, and a large number of closed or open cells are formed during the reaction process. It has multiple characteristics such as light weight, thermal insulation, cushioning, sealing, etc., and is one of the most widely used synthetic foam materials at present, penetrating into multiple fields such as industry, construction, home, transportation, etc.
[0003] The polyurethane foam is usually prepared from a polyurethane foam composition, but the polyurethane foam prepared from the existing polyurethane foam composition has a high thermal conductivity, which needs to be further improved. SUMMARY
[0004] Therefore, the present application provides a polyurethane foam composition, a polyurethane foam and a preparation method thereof, and a refrigeration device.
[0005] The polyurethane foam composition provided by the present application comprises component A and component B, the component A comprises polyol, blowing agent, modified hollow glass microsphere, modified nanosilica and additive, the additive comprises one or more of catalyst, stabilizer and antioxidant, and the component B comprises isocyanate, wherein, The content of the polyol is 28-35 parts by mass, the content of the blowing agent is 12-18 parts, the content of the modified hollow glass microsphere is 8-15 parts, the content of the modified nanosilica is 6-10 parts, the content of the catalyst is 0.5-0.9 parts, the content of the stabilizer is 1.2-1.6 parts, the content of the antioxidant is 0.5-0.7 parts, and the content of the isocyanate is 38-45 parts.
[0006] Optionally, in some embodiments, the modified hollow glass microsphere comprises hollow glass microspheres grafted with a silane coupling agent, and the hollow glass microspheres grafted with the silane coupling agent comprise hollow glass microspheres and a first silane coupling agent on the surface of the hollow glass microspheres. And / or, the modified nanosilica comprises nanosilica grafted with a silane coupling agent, and the nanosilica grafted with the silane coupling agent comprises nanosilica and a second silane coupling agent on the surface of the nanosilica.
[0007] Optionally, in some embodiments, the average particle size of the hollow glass microspheres is 50-80 µm. and / or, the hollow glass microsphere has a D 50 of 55-75 pm; and / or, the nanosilica has an average particle size of 15-25 nm; and / or, the nanosilica has a D 50 of 5-25 nm; and / or, the nanosilica has a D 90 of 80-250 nm; and / or, the hollow glass microsphere grafted and modified by the silane coupling agent has a grafting rate of the silane coupling agent of 1.8wt%-12wt%; and / or, the nanosilica grafted and modified by the silane coupling agent has a grafting rate of the silane coupling agent of 2wt%-15wt%; and / or, the first silane coupling agent and the second silane coupling agent each independently comprise one or more of g-aminopropyltriethoxysilane, g-glycidyloxypropyltrimethoxysilane, g-(methacryloyloxy)propyltrimethoxysilane, ureidopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, bis(3-trimethoxysilylpropyl)amine, g-mercaptopropyltriethoxysilane, vinyltriethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane.
[0008] Optionally, in some embodiments, the polyol comprises a polyether polyol, wherein, the polyether polyol has a hydroxyl value of 51-61 mgKOH / g; and / or, the polyether polyol comprises a long-chain polyether alcohol, the long-chain polyether alcohol has a molecular weight of 2000-5000, and the long-chain polyether alcohol comprises polypropylene glycol.
[0009] Optionally, in some embodiments, the isocyanate comprises polymeric diphenylmethane diisocyanate, the polymeric diphenylmethane diisocyanate has a functionality of 2.6-3.0, the polymeric diphenylmethane diisocyanate has a viscosity of 150-210 mPa s, and the polymeric diphenylmethane diisocyanate has a content of -NCO of 30-32wt%; And / or, the catalyst comprises one or more of an amine catalyst and an organic metal compound catalyst, the amine catalyst comprises one or more of triethylenediamine, dibutyltin dilaurate, N,N-dimethylcyclohexylamine, N,N,N',N'-tetramethylethylenediamine, dimethylethanolamine, N,N-dimethylbenzylamine, 2,2'-dimorpholinodiethylether, the organic metal compound catalyst comprises one or more of zinc octoate, bismuth iso-octoate, tetrabutyl titanate, lead naphthenate; And / or, the stabilizer comprises a silicone oil, the silicone oil has a viscosity of 200-300 mPa s at 25 DEG C, a surface tension of 18-23 mN / m, the silicone oil comprises one or more of Momentive L-6900 silicone oil, Momentive L-7001 silicone oil, Momentive L-580 silicone oil, Momentive L-620 silicone oil, Dow Corning DC-193 silicone oil, Dow Corning DC-5043 silicone oil, Dow Corning DC-198 silicone oil, Suzhou Sider SD-613 silicone oil, Suzhou Sider SD-624 silicone oil, BYK-346 silicone oil, DeMei FM-9901 silicone oil, Wacker AK-8803 silicone oil, Wacker AK-8815 silicone oil, fluorine-containing modified silicone oil, the fluorine-containing modified silicone oil comprises one or more of hydroxyl-terminated fluorosilicone oil, fluorine-containing polyglyceryl ether-polydimethylsiloxane block copolymer; And / or, the foaming agent comprises one or more of a physical foaming agent and a chemical foaming agent, the physical foaming agent comprises one or more of a hydrocarbon physical foaming agent, a fluoroalkene foaming agent, an ester foaming agent, an alcohol ether foaming agent, a bio-based foaming agent, a supercritical fluid foaming agent, wherein the hydrocarbon physical foaming agent comprises one or more of cyclopentane, isopentane, n-pentane, cyclohexane, the fluoroalkene foaming agent comprises one or more of 1-chloro-3,3,3-trifluoropropene foaming agent, 2,3,3,3-tetrafluoropropene foaming agent, 1,3,3,3-tetrafluoropropene foaming agent, the ester foaming agent comprises one or more of ethyl acetate, dimethyl carbonate, the alcohol ether foaming agent comprises one or more of dimethyl ether, methoxyethanol, the bio-based foaming agent comprises one or more of limonene derivatives, turpentine-based compounds, the supercritical fluid foaming agent comprises supercritical CO2, the chemical foaming agent comprises one or more of water, formic acid, oxalic acid; And / or, the antioxidant comprises one or more of hindered phenolic antioxidant, phosphite antioxidant, thioester antioxidant, amine antioxidant, the hindered phenolic antioxidant comprises one or more of tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid octadecyl ester, N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, triethylene glycol bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, the phosphite antioxidant comprises one or more of tris[2.4-di-tert-butylphenyl]phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, the thioester antioxidant comprises one or more of dilauryl thiodipropionate, distearyl thiodipropionate, the amine antioxidant comprises one or more of N-isopropyl-N'-phenyl-p-phenylenediamine, N,N'-bis(β-naphthyl)-p-phenylenediamine.
[0010] Correspondingly, the application further provides a preparation method of the polyurethane foam, comprising the following steps: providing the polyurethane foam composition, mixing component A and component B in the polyurethane foam composition, and foaming under the first air pressure; depressurizing to the second air pressure, foaming under the second air pressure, and obtaining the polyurethane foam.
[0011] Optionally, in some embodiments, the first air pressure is 1-1.2 Mpa; And / or, the second air pressure is 0.2-0.4 Mpa; And / or, the depressurization rate when depressurizing to the second air pressure is 0.1-0.14 MPa / min; And / or, the foaming time under the first air pressure is 55-65 seconds; And / or, the foaming time under the second air pressure is 2.7-3.3 min; And / or, the foaming temperature under the first air pressure is 46-50°C; And / or, the foaming temperature under the second air pressure is 56-60°C; And / or, the air pressure when mixing component A and component B in the polyurethane foam composition is 16-20 Mpa.
[0012] Optionally, in some embodiments, the method further comprises, after the step of foaming under pressure at the second air pressure and before the step of obtaining the polyurethane foam: sequentially performing a first heat curing process and a second heat curing process, the first heat curing process having a temperature lower than the temperature of the second heat curing process, wherein, the temperature of the first heat curing process is 68-72℃, and the time of the first heat curing process is 13-17h; and / or, the temperature of the second heat curing process is 72-77℃, and the time of the second heat curing process is 26-30h.
[0013] Optionally, in some embodiments, the preparation of the component A comprises the following steps: mixing a hollow glass microsphere dispersion liquid with a first silane coupling agent, the hollow glass microsphere dispersion liquid comprising hollow glass microspheres, a first heat treatment, grafting the first silane coupling agent to the surface of the hollow glass microspheres, to obtain modified hollow glass microspheres; mixing a nano-silica dispersion liquid with a second silane coupling agent, the nano-silica dispersion liquid comprising nano-silica, a second heat treatment, grafting the second silane coupling agent to the surface of the nano-silica, to obtain modified nano-silica; mixing the modified hollow glass microspheres, the modified nano-silica, and additives, to obtain a mixed liquid; mixing the mixed liquid with a foaming agent, to obtain the component A.
[0014] Optionally, in some embodiments, the temperature of the first heat treatment and the temperature of the second heat treatment are each independently 70-80℃; and / or, the time of the first heat treatment and the time of the second heat treatment are each independently 2-3h; and / or, the temperature of mixing the modified hollow glass microspheres, the modified nano-silica, and additives is 20-24℃; and / or, the first silane coupling agent accounts for 2-15% of the mass of the hollow glass microspheres; and / or, the second silane coupling agent accounts for 2-20% of the mass of the nano-silica.
[0015] Correspondingly, the present application also provides a polyurethane foam, which is obtained by foaming the polyurethane foam composition or prepared by the preparation method.
[0016] Optionally, in some embodiments, the polyurethane foam comprises a foam matrix and fillers dispersed in the foam matrix, the fillers comprising modified hollow glass microspheres and modified nano-silica, and the material of the foam matrix comprising polyurethane.
[0017] Optionally, in some embodiments, the closed cell ratio of the polyurethane foam is greater than or equal to 97%; And / or, the cell diameter of the cells in the polyurethane foam is 80-150 μm; And / or, the weight average degree of polymerization of the polyurethane is 3000-6000; And / or, the thermal conductivity of the polyurethane foam is less than or equal to 0.017 W / (m K); And / or, in the polyurethane foam, the content of the polyurethane is 50wt%-70wt%, the content of the modified hollow glass microsphere is 20wt%-35wt%, and the content of the modified nanosilica is 5wt%-15wt%.
[0018] Correspondingly, the application also provides a refrigeration device comprising the polyurethane foam.
[0019] The polyurethane foam composition described in the application can effectively reduce the thermal conductivity of the polyurethane foam prepared from the polyurethane foam composition through the synergistic effect between the components and their contents, break through the thermal conductivity bottleneck of the existing foaming agent and filler system, reduce the thermal conductivity of the polyurethane foam to below 0.017 W / (m K), and meet the purpose of long-term use of high-energy-efficiency refrigerators; on the other hand, it can also solve the interface compatibility problem between the high-load filler and the foam matrix of the polyurethane foam prepared from the polyurethane foam composition, effectively improve the compression strength of the polyurethane foam and the higher compression strength stability; on the other hand, the polyurethane foam composition is suitable for high filler system (i.e. system with high filler content), and is conducive to making the cell size of the prepared polyurethane foam have higher uniformity. In addition, the polyurethane foam composition described in the application can also take into account environmental protection and cost controllability, has higher environmental protection and lower cost. BRIEF DESCRIPTION OF DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the application, the drawings needed in the embodiment description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor.
[0021] Figure 1 is a preparation method flow chart of a polyurethane foam provided by the embodiments of the application; Figure 2 is a preparation method flow chart of component A provided by the embodiments of the application. DETAILED DESCRIPTION
[0022] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of this application and are not intended to limit this application.
[0023] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state, specifically the drawing directions in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish a numerical order.
[0024] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.
[0025] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c," or "at least one of a, b, and c," can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0026] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, whichever applies. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.
[0027] The polyurethane foam prepared by using the existing polyurethane foam composition has problems of high thermal conductivity and weak mechanical property. The process stability of the traditional polyurethane foam composition is poor, and the composition is not suitable for high filler system. The process stability is poor, and the foam performance fluctuates due to the phenomena of filler sedimentation and foam rupture. Therefore, the technical problem of poor process stability needs to be further improved.
[0028] The technical scheme of the present application is as follows: In a first aspect, the present application provides a polyurethane foam composition, which is mainly used for preparing polyurethane foam. The polyurethane foam composition comprises component A and component B. The component A comprises polyol, blowing agent (LBA), modified hollow glass microsphere, modified nanosilica and additive, wherein the additive comprises one or more of catalyst, stabilizer and antioxidant. The component B comprises isocyanate.
[0029] In some embodiments, the modified hollow glass microsphere comprises hollow glass microsphere grafted and modified by silane coupling agent. It can be understood that the hollow glass microsphere grafted and modified by silane coupling agent comprises hollow glass microsphere (HGM) and first silane coupling agent on the surface of the hollow glass microsphere. The first silane coupling agent modifies the surface of the hollow glass microsphere. The addition of the modified hollow glass microsphere is beneficial to form macroscopic thermal insulation skeleton and block solid phase thermal conduction when the polyurethane foam is prepared by using the polyurethane foam composition, thereby improving the thermal insulation efficiency.
[0030] In some embodiments, the modified nanosilica comprises nanosilica grafted and modified by silane coupling agent. It can be understood that the nanosilica grafted and modified by silane coupling agent comprises nanosilica and second silane coupling agent on the surface of the nanosilica. The second silane coupling agent modifies the surface of the nanosilica. The addition of the modified nanosilica is beneficial to microcell nucleation and cell refinement when the polyurethane foam is prepared by using the polyurethane foam composition, thereby reducing the heat conduction path and improving the thermal insulation effect.
[0031] It can be understood that the modified hollow glass microsphere and the modified nanosilica are fillers in the polyurethane foam composition.
[0032] In some embodiments, in the polyurethane foam composition, the content of the polyol is 28-35 parts by mass, the content of the foaming agent is 12-18 parts, the content of the modified hollow glass microsphere is 8-15 parts, the content of the modified nanosilica is 6-10 parts, the content of the catalyst is 0.5-0.9 parts, the content of the stabilizer is 1.2-1.6 parts, the content of the antioxidant is 0.5-0.7 parts, and the content of the isocyanate is 38-45 parts.
[0033] The polyurethane foam composition described in the present application can effectively reduce the thermal conductivity of the polyurethane foam prepared from the polyurethane foam composition through the synergistic effect between the components and their contents, break through the thermal conductivity bottleneck of the existing foaming agent and filler system, and reduce the thermal conductivity of the polyurethane foam to below 0.017 W / (m K), which can meet the long-term use purpose of high-energy-efficiency refrigerators. On the other hand, the interfacial compatibility problem between the high-load filler and the foam matrix of the polyurethane foam prepared from the polyurethane foam composition can be solved, and the compression strength and the high compression strength stability of the polyurethane foam can be effectively improved. On the other hand, the polyurethane foam composition is suitable for a high filler system (i.e., a system with a high filler content), and is conducive to making the cell size of the prepared polyurethane foam have high uniformity. In addition, the polyurethane foam composition described in the present application can also take into account environmental protection and cost controllability, and has high environmental protection and low cost.
[0034] As an example, in some embodiments, the polyol is present in an amount of 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, and any value or range between any two of these values, etc.; the blowing agent is present in an amount of 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, and any value or range between any two of these values, etc.; the modified hollow glass microsphere is present in an amount of 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, and any value or range between any two of these values, etc.; the modified nano-silica is present in an amount of 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, and any value or range between any two of these values, etc.; the catalyst is present in an amount of 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, and any value or range between any two of these values, etc.; the stabilizer is present in an amount of 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, and any value or range between any two of these values, etc.; the antioxidant is present in an amount of 0.5 parts, 0.6 parts, 0.7 parts, and any value or range between any two of these values, etc.; and the isocyanate is present in an amount of 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, and any value or range between any two of these values, etc.
[0035] In some embodiments, the isocyanate comprises polymeric diphenylmethane diisocyanate (polymeric MDI). In the polymeric MDI, the content of -NCO is 30-32 wt%, for example, 30 wt%, 30.5 wt%, 31 wt%, 31.5 wt%, 32 wt%, and any value or range between any two of these values, etc.; the functionality of the polymeric MDI is 2.6-3.0, for example, 2.6, 2.7, 2.8, 2.9, 3.0, and any value or range between any two of these values, etc.; the viscosity of the polymeric MDI is 150-210 mPa s, for example, 150 mPa s, 160 mPa s, 170 mPa s, 180 mPa s, 190 mPa s, 200 mPa s, 210 mPa s, and any value or range between any two of these values, etc. Within the range, in combination with other components in the polyurethane polymer, it is more conducive to preparing a polyurethane foam with lower thermal conductivity, higher compressive strength, etc.
[0036] In some embodiments, the polyol includes a polyether polyol. The polyether polyol can provide hydroxyl groups that react with isocyanate, which is advantageous for securing the toughness of the foam matrix of the polyurethane foam prepared, and for adapting the foam matrix to high filler dispersion.
[0037] Further, in some embodiments, the polyether polyol includes, but is not limited to, a long chain polyether alcohol. The long chain polyether alcohol has a molecular weight of 2000-5000, for example, 2000, 3000, 4000, 5000, and any value or range between any two of the values. The long chain polyether alcohol includes, but is not limited to, polypropylene glycol (PPG). As an example, the polypropylene glycol includes, but is not limited to, one or more of PPG-2000, PPG-3000. In some embodiments, the polyether polyol has a hydroxyl value of 51-61 mgKOH / g, for example, 51 mgKOH / g, 52 mgKOH / g, 53 mgKOH / g, 54 mgKOH / g, 55 mgKOH / g, 56 mgKOH / g, 57 mgKOH / g, 58 mgKOH / g, 59 mgKOH / g, 60 mgKOH / g, 61 mgKOH / g, and any value or range between any two of the values. The range accommodates the fluctuations in industrial production of PPG-2000 and PPG-3000 type polyether polyols, and within 51-61 mgKOH / g, the toughness of the foam matrix and high filler dispersion can be secured. The range corresponds to long chain polyether alcohol, with moderate hydroxyl density and controllable reaction rate, which can avoid too fast gelation and too slow curing, and can secure sufficient crosslinking with isocyanate to form a complete cell structure, and can accommodate high filler (modified hollow glass microbeads, nano-silica) dispersion due to the long molecular chain to improve the toughness of the matrix, and ultimately achieve a synergy of low thermal conductivity and high compressive strength to match the requirements of low thermal conductivity and high mechanical strength of the refrigerator insulation layer. If the hydroxyl value is too high, the hydroxyl density of the polyether polyol is large, and the reaction with isocyanate is too fast, which can easily lead to rapid crosslinking and curing, resulting in insufficient cell expansion (formation of dense small cells), a significant increase in thermal conductivity, and a loss of insulation advantage; and the large crosslinking density can make the foam matrix brittle, and when the high filler is dispersed, interface cracks can be easily generated, resulting in a decrease in compressive strength and failure to meet the strength requirements of the refrigerator. If the hydroxyl value is too low, the number of hydroxyl groups of the polyether polyol is insufficient, and the reaction with isocyanate is not sufficient, which can result in incomplete curing, cell wall rupture to form connected pores, a sharp increase in thermal conductivity, and a low compressive strength of the matrix, which can easily lead to the agglomeration of high fillers, further deteriorating the structural stability.
[0038] It should be noted that in this application, the hydroxyl value of the polyether polyol is obtained by detection according to the national standard GB / T 12008.3-2009.
[0039] In some embodiments, the foaming agent includes but is not limited to one or more of physical foaming agents and chemical foaming agents, the physical foaming agents include but are not limited to one or more of hydrocarbon physical foaming agents, fluoroalkene foaming agents, ester foaming agents, alcohol ether foaming agents, bio-based foaming agents, supercritical fluid foaming agents, wherein the hydrocarbon physical foaming agents include but are not limited to one or more of cyclopentane, isopentane, n-pentane, cyclohexane, the fluoroalkene foaming agents include but are not limited to one or more of HCFO-1233zd (1-chloro-3,3,3-trifluoropropene foaming agent), HFO-1234yf (2,3,3,3-tetrafluoropropene foaming agent), HFO-1234ze (1,3,3,3-tetrafluoropropene foaming agent), the ester foaming agents include but are not limited to one or more of ethyl acetate, dimethyl carbonate, the alcohol ether foaming agents include but are not limited to one or more of dimethyl ether, methoxy ethanol, the bio-based foaming agents include but are not limited to one or more of limonene derivatives, turpentine-based compounds, the supercritical fluid foaming agents include but are not limited to supercritical CO2. The chemical foaming agent includes but is not limited to one or more of water, formic acid, oxalic acid. The foaming agent is conducive to strengthening the gas phase insulation, reducing the gas phase thermal conductivity.
[0040] In some embodiments, the hollow glass microspheres grafted with silane coupling agent have a grafting rate of 1.8wt%~12wt%, for example, 1.8wt%, 2wt%, 3wt%, 5wt%, 6wt%, 8wt%, 10wt%, 12wt% and a value or range between any two of the values, etc. Within the range, it is more conducive to forming a macroscopic thermal insulation skeleton, more conducive to blocking the solid phase thermal conduction, and thus more conducive to improving the thermal insulation efficiency.
[0041] It should be noted that in this application, the grafting rate of the hollow glass microspheres grafted with silane coupling agent is detected by the group standard T / SDAMA006-2024 "Determination of Grafting Rate of Modified Inorganic Powder Materials by Thermogravimetry".
[0042] In some embodiments, the average particle size of the hollow glass microspheres is 50~80µm, for example, 50µm, 55µm, 60µm, 65µm, 70µm, 78µm, 80µm and a value or range between any two of the values, etc. Within the range, it is more conducive to forming a macroscopic thermal insulation skeleton, more conducive to blocking the solid phase thermal conduction, and thus more conducive to improving the thermal insulation efficiency.
[0043] In some embodiments, the hollow glass microspheres have a D 50For 55~75μm, examples: 55μm, 58μm, 62μm, 68μm, 72μm, 75μm, etc. The range adapts to the industrial production deviation, which is beneficial to guarantee the dispersibility of hollow glass microspheres in polyurethane foam and the stability of cell structure.
[0044] In some embodiments, the grafting rate of the silane coupling agent in the silane coupling agent graft-modified nanosilica is 2wt%~15wt%, for example, 2wt%, 3wt%, 5wt%, 6wt%, 8wt%, 10wt%, 12wt%, 13wt%, 15wt%. Within the range, it is more beneficial to nucleate microcell, more beneficial to refine the cell, thereby more beneficial to reduce the heat conduction path, thereby improving the heat insulation effect, and also can take into account the dispersibility of the filler and the synergy of the thermal-mechanical properties of the polyurethane foam.
[0045] It should be noted that in this application, the grafting rate of the hollow glass microspheres grafted with silane coupling agent is detected by the group standard T / SDAMA006-2024 "Determination of grafting rate of modified inorganic powder materials by thermogravimetry".
[0046] In some embodiments, the average particle size of the nanosilica is 15~25 nm, for example, 15 nm, 16 nm, 18 nm, 20 nm, 22 nm, 23 nm, 25 nm, and a value or range between any two of the values, etc. Within the range, it is more beneficial to avoid filler agglomeration, guarantee the dispersibility of the filler in the polyurethane foam prepared and the stability of the foam structure.
[0047] In some embodiments, the D 50 For 5~25 nm, for example, 5 nm, 6 nm, 10 nm, 12 nm, 13 nm, 15 nm, 16 nm, 18 nm, 20 nm, 23 nm, 25 nm, and a value or range between any two of the values, etc. Within the range, it is more beneficial to avoid filler agglomeration, guarantee the dispersibility of the filler in the polyurethane foam prepared and the stability of the foam structure.
[0048] In some embodiments, the D 90 For 80~250 nm, for example, 80 nm, 100 nm, 130 nm, 150 nm, 180 nm, 200 nm, 130 nm, 250 nm, and a value or range between any two of the values, etc. Within the range, it is more beneficial to avoid filler agglomeration, guarantee the dispersibility of the filler in the polyurethane foam prepared and the stability of the foam structure.
[0049] It should be noted that the particle size of the particles in the present application is detected and tested by a laser particle size analyzer.
[0050] In some embodiments, the first silane coupling agent and the second silane coupling agent each independently include, but are not limited to, one or more of KH550 (γ-aminopropyltriethoxysilane), KH560 (γ-glycidoxypropyltrimethoxysilane), KH570 (γ-(methacryloyloxy)propyltrimethoxysilane), KH591 (ureidopropyltriethoxysilane), KH792 (N-(2-aminoethyl)-3-aminopropyltrimethoxysilane), KH170 (bis(3-trimethoxysilylpropyl)amine), KH580 (γ-mercaptopropyltriethoxysilane), A-151 (vinyltriethoxysilane), KH602 (N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane).
[0051] In the modified hollow glass microbeads, the inorganic end alkoxy of the first silane coupling agent can react with the silicon hydroxyl on the surface of the hollow glass microbeads, and the organic end (amino, epoxy, mercapto, vinyl, etc.) can be bonded with the -NCO or -OH in the polyurethane in the foam matrix, thereby effectively enhancing the compatibility of the hollow glass microbeads with the foam matrix and effectively constructing a thermal insulation skeleton.
[0052] In the modified nanosilica, the inorganic end alkoxy of the second silane coupling agent can react with the silicon hydroxyl on the surface of the nanosilica, and the organic end (amino, epoxy, mercapto, vinyl, etc.) can be bonded with the -NCO or -OH in the polyurethane in the foam matrix, thereby effectively enhancing the compatibility of the nanosilica with the foam matrix and effectively constructing a thermal insulation skeleton.
[0053] In some embodiments, the catalyst includes, but is not limited to, one or more of amine catalysts and organometallic compound catalysts. The amine catalysts include, but are not limited to, one or more of triethylenediamine, dibutyltin dilaurate, N,N-dimethylcyclohexylamine (DMCHA), N,N,N',N'-tetramethylethylenediamine (TMEDA), dimethyl ethanolamine (DMEA), N,N-dimethylbenzylamine (DMB), 2,2'-dimorpholinodiethylether (DMDEE). The organometallic compound catalysts include, but are not limited to, one or more of zinc octoate, bismuth isooctoate, tetrabutyl titanate, lead naphthenate. The catalyst can effectively regulate the foaming rate and curing rate of the polyurethane foam composition, which is conducive to avoiding the occurrence of cell collapse of the polyurethane foam composition with high filler content when preparing the polyurethane foam, and effectively avoiding the occurrence of cell collapse of the polyurethane foam when in use.
[0054] In at least some embodiments, the catalyst is a mixed catalyst comprising triethylenediamine and dibutyltin dilaurate at the same time, and the content of triethylenediamine in the polyurethane foam composition is 0.3-0.5 parts by mass, and the content of dibutyltin dilaurate is 0.2-0.4 parts by mass. In this way, the foaming rate and curing rate of the polyurethane foam composition can be more effectively controlled, which is more conducive to avoiding the occurrence of cell collapse of the polyurethane foam composition with high filler content during the preparation of polyurethane foam, and more effectively avoiding the occurrence of cell collapse of polyurethane foam during use.
[0055] In some embodiments, the stabilizer includes but is not limited to silicone oil, which includes but is not limited to one or more of Momentive L-6900 silicone oil, Momentive L-7001 silicone oil, Momentive L-580 silicone oil, Momentive L-620 silicone oil, Dow Corning DC-193 silicone oil, Dow Corning DC-5043 silicone oil, Dow Corning DC-198 silicone oil, Suzhou Sida SD-613 silicone oil, Suzhou Sida SD-624 silicone oil, BYK-346 silicone oil, Dema FM-9901 silicone oil, Wacker AK-8803 silicone oil, Wacker AK-8815 silicone oil, fluorine-containing modified silicone oil. The fluorine-containing modified silicone oil includes but is not limited to one or more of hydroxyl-terminated fluorosilicone oil, fluorine-containing polyglyceryl ether-polydimethylsiloxane block copolymer. The stabilizer can effectively stabilize the ultra-fine cell wall, effectively avoid open cells, and effectively improve the closed cell rate of the polyurethane foam.
[0056] In some embodiments, the viscosity of the silicone oil at 25°C is 200-300 mPa s, for example, 200 mPa s, 220 mPa s, 230 mPa s, 250 mPa s, 260 mPa s, 280 mPa s, 300 mPa s, and any two numerical values or ranges therebetween, etc. The surface tension of the silicone oil is 18-23 mN / m, for example, 18 mN / m, 19 mN / m, 20 mN / m, 21 mN / m, 22 mN / m, 23 mN / m, and any two numerical values or ranges therebetween, etc. Within the range, the ultra-fine cell wall can be more effectively stabilized by moderate tension, open cells can be more effectively avoided, the closed cell rate of the polyurethane foam can be more effectively improved, and the compatibility of the system can also be more effectively ensured to meet the high filler foaming demand.
[0057] In some embodiments, the antioxidant includes, but is not limited to, one or more of hindered phenolic antioxidant, phosphite antioxidant, thioester antioxidant, amine antioxidant. The hindered phenolic antioxidant includes, but is not limited to, one or more of antioxidant 1010 (tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]pentaerythritol ester), antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloctadecyl ester), antioxidant 1098 (N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine), antioxidant 245 (triethyleneglycol bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]), antioxidant 3114 (1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione). The phosphite antioxidant includes, but is not limited to, one or more of antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 626 (bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite). The thioester antioxidant includes, but is not limited to, one or more of antioxidant DLTP (dilauryl thiodipropionate), antioxidant DSTP (distearyl thiodipropionate). The amine antioxidant includes, but is not limited to, one or more of antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine), antioxidant 4020 (N,N'-bis(β-naphthyl)-p-phenylenediamine). The antioxidant can effectively improve the long-term aging resistance of the polyurethane foam prepared from the polyurethane foam composition, and is conducive to making the polyurethane foam have a long-term good heat insulation effect.
[0058] In a second aspect, referring to Figure 1 The application also provides a method for preparing a polyurethane foam, including the following steps: Step S11, providing a polyurethane foam composition, mixing component A and component B in the polyurethane foam composition, and foaming under pressure at a first air pressure; Step S12, reducing the pressure to a second air pressure, foaming under pressure at the second air pressure, and obtaining a polyurethane foam.
[0059] The polyurethane foam includes a foam matrix and a filler dispersed in the foam matrix, the filler includes the modified hollow glass microsphere and the modified nanosilica, and the material of the foam matrix includes polyurethane.
[0060] The polyurethane foam composition is described above, and is not repeated here.
[0061] In the preparation method, the pressure holding foaming at the first air pressure is a high-pressure nucleation stage, which is beneficial to the nucleation of ultrafine cells; and the pressure holding foaming at the second air pressure is a low-pressure growth stage, which is beneficial to the uniform growth of the cells and effectively avoids agglomeration. In this way, the gradient pressure preparation process is beneficial to the high uniformity of the cells in the prepared polyurethane foam.
[0062] The preparation method of the polyurethane foam described in the present application uses the polyurethane foam composition described above as raw material, and utilizes the synergistic effect of "high-load double-modified filler (modified hollow glass microbeads and modified nano-silica) + low-GWP (global warming potential) foaming agent + gradient pressure foaming process", which can effectively improve the interfacial compatibility of the filler and the foam matrix, and also make the cells in the polyurethane foam have higher uniformity, achieving the synergistic balance of "mechanical enhancement effect of high-load filler + low thermal conductivity effect of LBA + cell uniformization effect of gradient pressure foaming process", effectively reducing the thermal conductivity of the polyurethane foam, breaking through the thermal conductivity bottleneck of the existing foaming agent and filler system, and reducing the thermal conductivity of the polyurethane foam to below 0.017 W / (m K), which can meet the long-term use purpose of high-energy-efficiency refrigerators, and also effectively improve the compression strength and compression strength stability of the polyurethane foam.
[0063] In some embodiments, the air pressure for mixing component A and component B in the polyurethane foam composition is 16-20 Mpa, for example, 16 Mpa, 17 Mpa, 18 Mpa, 19 Mpa, 20 Mpa, and a numerical range between any two of the values. Within the range, it is more beneficial to the nucleation of ultrafine cells.
[0064] In some embodiments, the first air pressure is 1-1.2 Mpa, for example, 1 Mpa, 1.1 Mpa, 1.2 Mpa, and a numerical value or range between any two of the values; the time for pressure holding foaming at the first air pressure is 55-65 seconds, for example, 55 seconds, 60 seconds, 65 seconds, and a numerical value or range between any two of the values.
[0065] Within the first air pressure and the range of the first air pressure, it is more beneficial to the nucleation of ultrafine cells, and more beneficial to the high uniformity of the cells in the prepared polyurethane foam.
[0066] In some embodiments, the temperature for pressure holding foaming at the first air pressure is 46-50℃, for example, 46℃, 47℃, 48℃, 49℃, 50℃, and a numerical value or range between any two of the values. Within the temperature range, it is more beneficial to the nucleation of ultrafine cells, and more beneficial to the high uniformity of the cells in the prepared polyurethane foam.
[0067] In some embodiments, the second gas pressure is 0.2-0.4 MPa, for example, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa, and a value or range between any two of the values, etc.; the time for pressure foaming at the second gas pressure is 2.7-3.3 min, for example, 2.7 min, 2.8 min, 2.9 min, 3.0 min, 3.1 min, 3.2 min, 3.3 min, and a value or range between any two of the values, etc. Within the range of the pressure and time, it is more conducive to the uniform growth of the cells and more conducive to avoiding agglomeration, thereby more conducive to making the cells in the polyurethane foam prepared have higher uniformity.
[0068] In some embodiments, the depressurization rate to the second gas pressure is 0.1-0.14 MPa / min, for example, 0.1 MPa / min, 0.11 MPa / min, 0.12 MPa / min, 0.13 MPa / min, 0.14 MPa / min, and a value or range between any two of the values, etc. Within the range of the depressurization rate, it is more conducive to the uniform growth of the cells and more conducive to avoiding agglomeration, thereby more conducive to making the cells in the polyurethane foam prepared have higher uniformity.
[0069] In some embodiments, the temperature for pressure foaming at the second gas pressure is 56-60℃, for example, 56℃, 57℃, 58℃, 59℃, 60℃, and a value or range between any two of the values, etc. Within the range of the temperature, it is more conducive to the uniform growth of the cells and more conducive to avoiding agglomeration, thereby more conducive to making the cells in the polyurethane foam prepared have higher uniformity.
[0070] In some embodiments, after pressure foaming at the second gas pressure and before obtaining the polyurethane foam, further comprising: sequentially performing a first heat curing treatment and a second heat curing treatment, wherein the temperature of the first heat curing treatment is lower than the temperature of the second heat curing treatment. The segmented curing process is conducive to ensuring that the polyurethane foam has higher strength and stability under high filler load.
[0071] In some embodiments, the temperature of the first heat curing treatment is 68-72℃, for example, 68℃, 69℃, 70℃, 71℃, 72℃, and a value or range between any two of the values, etc.; the time of the first heat curing treatment is 13-17 h, for example, 13 h, 14 h, 15 h, 16 h, 17 h, and a value or range between any two of the values, etc. Within the range of the temperature and time, the foaming product can be preliminarily cured to fix the cell structure.
[0072] In some embodiments, the temperature of the second heat curing treatment is 72-77℃, for example, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, and a value or range between any two of the values, etc.; the time of the second heat curing treatment is 26-30 h, for example, 26 h, 27 h, 28 h, 29 h, 30 h, and a value or range between any two of the values, etc. Within the temperature and time range, the foaming product can be completely cured, which is beneficial to the reinforcement of the interface bonding.
[0073] In some embodiments, referring to Figure 2 , the preparation of the component A comprises the following steps: Step S01, mixing a hollow glass microsphere dispersion liquid with a first silane coupling agent, the hollow glass microsphere dispersion liquid comprising hollow glass microspheres, a first heat treatment, grafting the first silane coupling agent to the surface of the hollow glass microspheres, to obtain modified hollow glass microspheres; Step S02, mixing a nano-silica dispersion liquid with a second silane coupling agent, the nano-silica dispersion liquid comprising nano-silica, a second heat treatment, grafting the second silane coupling agent to the surface of the nano-silica, to obtain modified nano-silica; Step S03, mixing the modified hollow glass microspheres, the modified nano-silica, a polyol, and an additive, to obtain a mixed liquid; Step S04, mixing the mixed liquid with a foaming agent, to obtain the component A.
[0074] In some embodiments, the temperature of the first heat treatment and the temperature of the second heat treatment are each independently 70-80℃, for example, 70℃, 75℃, 80℃, and a value or range between any two of the values, etc.; the time of the first heat treatment and the time of the second heat treatment are each independently 2-3 h, for example, 2 h, 2.5 h, 3 h, and a value or range between any two of the values, etc.
[0075] In some embodiments, the temperature of mixing the modified hollow glass microspheres, the modified nano-silica, and the additive is 20-24℃, for example, 20℃, 21℃, 22℃, 23℃, 24℃, and a value or range between any two of the values, etc. Within the temperature range, it is beneficial to avoid early reaction under high filler.
[0076] In some embodiments, the first silane coupling agent accounts for 2-15% of the mass of the hollow glass microspheres, for example, 2%, 5%, 8%, 10%, 13%, 15%, and a value or range between any two of the values, etc.
[0077] In some embodiments, the second silane coupling agent accounts for 2% to 20% of the mass of the nanosilica, for example, 2%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, and a value or range between any two of the values, etc.
[0078] In a third aspect, the embodiments of the present application further provide a polyurethane foam, which is prepared from the polyurethane foam composition described above after foaming, or which is prepared from the method for preparing the polyurethane foam described above.
[0079] In some embodiments, the polyurethane foam includes a foam matrix and a filler dispersed in the foam matrix, the filler including modified hollow glass microbeads and modified nanosilica, and the material of the foam matrix including polyurethane.
[0080] The modified hollow glass microbeads and the modified nanosilica are described above, and will not be repeated here.
[0081] In some embodiments, the weight average degree of polymerization (Mw) of the polyurethane is 3000 to 6000. Within the range, it is beneficial to ensure that the foam matrix has both toughness (adapt to low hydroxyl value polyether) and structural stability (support filler dispersion), which meets the use requirements of the refrigerator insulation layer.
[0082] It should be noted that in the present application, the weight average degree of polymerization is determined by gel permeation chromatography (GPC).
[0083] In some embodiments, in the polyurethane foam, the content of the polyurethane is 50wt% to 70wt%, for example, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, and a value or range between any two of the values, etc.; the content of the modified hollow glass microbeads is 20wt% to 35wt%, for example, 20wt%, 25wt%, 30wt%, 35wt%, and a value or range between any two of the values, etc.; the content of the modified nanosilica is 5wt% to 15wt%, for example, 5wt%, 10wt%, 15wt%, and a value or range between any two of the values, etc. Within the range, the polyurethane foam can have higher thermal insulation and higher structural stability, etc.
[0084] In some embodiments, the thermal conductivity of the polyurethane foam is less than or equal to 0.017 W / (m K), for example, less than or equal to 0.017 W / (m K), less than or equal to 0.015 W / (m K), less than or equal to 0.013 W / (m K), less than or equal to 0.01 W / (m K), less than or equal to 0.01 W / (m
[0085] It should be noted that in the present application, the thermal conductivity of the polyurethane foam is detected by the national standard GB / T 10294-2008 "Determination of Steady-state Thermal Resistance and Related Properties of Thermal Insulation Materials - Guarded Hot Plate Method".
[0086] In some embodiments, the cell diameter of the cells in the polyurethane foam is 80-150 μm, for example, 80 μm, 100 μm, 120 μm, 130 μm, 150 μm, and a value or range between any two of the values, etc. The cells in the polyurethane foam have high uniformity, so that the polyurethane foam has high stability and heat insulation performance, and the performance fluctuation during use is small.
[0087] It should be noted that in the present application, the cell diameter is detected by the national standard GB / T 12811-2025 "Test Method for Average Cell Size of Rigid Foam Plastics".
[0088] In some embodiments, the closed cell rate of the polyurethane foam is greater than or equal to 97%, for example, 97%, 98%, 99%, 100%, and a value or range between any two of the values, etc. Within the range, it is beneficial to make the polyurethane foam have high stability and heat insulation performance, and the performance fluctuation during use is small.
[0089] The polyurethane foam described in the present application is prepared by using the polyurethane foam composition and the preparation method of the polyurethane foam described above. By using the ternary synergistic effect of "high-load double-modified filler (modified hollow glass microsphere and modified nano-silica) + low-GWP blowing agent + gradient pressure foaming process", the interfacial compatibility of the filler and the foam matrix can be effectively improved, and the cells in the polyurethane foam can have higher uniformity. The three synergistic balances of "mechanical enhancement effect of high-load filler + low thermal conductivity effect of LBA + cell uniformization effect of gradient pressure foaming process" are achieved, the thermal conductivity of the polyurethane foam is effectively reduced, the thermal conductivity bottleneck of the existing blowing agent and filler system is broken, and the thermal conductivity of the polyurethane foam can be reduced to less than or equal to 0.017 W / (m K), which can meet the long-term use purpose of high-energy-efficiency refrigerators, and can effectively improve the compression strength and compression strength stability of the polyurethane foam.
[0090] In a fourth aspect, the embodiments of the present application provide a refrigeration device, which has a thermal insulation layer, and the material of the thermal insulation layer is the polyurethane foam described above.
[0091] The refrigeration device can be a refrigerator, a refrigerator, or the like.
[0092] The refrigeration device described in the present application has the polyurethane foam described above, and has good heat insulation effect and high cold preservation effect.
[0093] The present application will be specifically described below through specific examples. The following examples are only part of the present application, and are not a limitation of the present application. The materials or reagents used in the examples and comparative examples of the present application are commercially available.
[0094] The preparation method of the polyurethane foam of each example of the present application includes the following steps: Step 1, hollow glass microspheres (HGM) are added to a mixed solvent of ethanol and water (the mass ratio of ethanol to water is 4:1), and ultrasonic dispersion is performed at 400W for 40min to completely remove surface impurities; silane coupling agent KH550 (3% of the mass of HGM) is added, and constant temperature stirring is performed at 75°C for 4h to enable KH550 to be fully grafted to the surface of HGM, and vacuum drying is performed at 85°C for 5h to obtain modified hollow glass microspheres; Step 2, nano-silicon dioxide (nano-SiO2) is added to a mixed solvent of ethanol and water (the mass ratio of ethanol to water is 4:1), and ultrasonic dispersion is performed at 400W for 30min; silane coupling agent KH560 (3% of the mass of nano-SiO2) is added, and the pH is adjusted to 4 with acetic acid, constant temperature stirring is performed at 75°C for 2h, and vacuum drying is performed at 85°C for 4h to obtain modified nano-silicon dioxide; the modified nano-silicon dioxide (nano-SiO2) is mixed with polyol PPG-3000, high-speed dispersion is performed at 3000r / min for 50min (dispersion temperature 45°C) to obtain a polyol dispersion liquid of modified nano-SiO2 with high dispersibility; Step 3, the polyol dispersion liquid of modified nano-SiO2, modified HGM, ethylenediamine, dibutyltin dilaurate mixed catalyst, foam stabilizer L-580, and antioxidant 1010 are added to a stirring tank, stirring is performed at 1000r / min for 15min to control the temperature of the mixed liquid to 22°C to obtain a mixed liquid; a foaming agent is added to the mixed liquid, and stirring is performed for 6min to obtain component A; Step 4, component A is mixed with isocyanate (polymeric MDI, component B) at a first air pressure of 18MPa under high pressure, injected into a refrigerator door body mold, and the mold temperature is controlled at a first air pressure of 1.1MPa and 48°C for 60s; Step 5, slowly reduce the pressure to a second air pressure of 0.3MPa at a rate of 0.12MPa / min, and control the temperature at 58°C for 3.0min to obtain a foaming product; Step 6, the foaming product is first cured (thermally cured) at 70°C for 15h, and then cured (thermally cured) at 75°C for 28h to obtain a polyurethane foam.
[0095] The raw material ratio of the polyurethane foam composition in Examples 1~3 is shown in Table 1 below: Table 1:
[0096] The hydroxyl value of PPG-3000 is 56 mgKOH / g, and the moisture content is 0.08%; the content of -NCO in polymeric MDI 5005 is 31wt%, and the viscosity at 25℃ is 180 mPa s; the purity of HCFO-1233zd is 99.9%, and the moisture content is 30ppm; the viscosity of L-580 is 250 mPa s, and the surface tension is 23 mN / m. The purity of antioxidant (1010) is 99.5%.
[0097] The process parameters in Examples 1~3 are shown in Table 2 below: Table 2:
[0098] Comparative Example 1 This comparative example is basically the same as Example 1, except that the hollow glass microbeads in this comparative example are not modified.
[0099] Comparative Example 2 This comparative example is basically the same as Example 1, except that the polyurethane foam composition in this comparative example does not contain modified hollow glass microbeads and modified nano-silica, and the content of the blowing agent is 18 parts.
[0100] Comparative Example 3 This comparative example is basically the same as Example 1, except that the polyurethane foam composition in this comparative example does not contain modified hollow glass microbeads, the nano-silica is not modified, and the content of the nano-silica is 8 parts.
[0101] Comparative Example 4 This comparative example is basically the same as Example 1, except that the foaming process for preparing the polyurethane foam in the polyurethane foam composition in this comparative example is 0.6MPa constant pressure foaming for 3.5min.
[0102] Comparative Example 5 This comparative example is basically the same as Example 1, except that the temperature of the first heat curing treatment and the temperature of the second heat curing treatment are both 53℃.
[0103] Comparative Example 6 The polyurethane foam composition (cyclopentane system) of the present comparative example comprises, by mass fraction: polyether polyol (PPG-3000) 30 parts, isocyanate (polymeric MDI 5005) 40 parts, foaming agent cyclopentane (high GWP, purity ≥95%) 20 parts, hollow glass microbeads (unmodified) 5 parts, catalyst single triethylenediamine 0.6 parts, stabilizer (silicone oil L-580) 1.2 parts, antioxidant (1010) 0.5 parts, wherein PPG-3000, polymeric MDI 5005, hollow glass microbeads, L-580, antioxidant 1010 are respectively the same as in Example 1.
[0104] The thermal conductivity, 25% compression strength, cell size, closed cell rate, density, strength retention rate after 100 times of temperature cycle, and thermal conductivity after 5 years of aging of the polyurethane foams of Examples 1-3 and Comparative Examples 1-6 were tested, and the test results of Examples 1-3 are shown in Table 3 below, and the test results of Comparative Examples 1-6 are shown in Table 4 below. The data of each performance was obtained by testing 5 parallel tests and then taking the average value.
[0105] The test method for thermal conductivity was determined by using the national standard GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials by Guarded Hot Plate Method".
[0106] The test method for 25% compression strength was determined by using the national standard GB / T 8813-2022 "Determination of Compression Properties of Rigid Foamed Plastics".
[0107] The test method for cell size was determined by using the national standard GB / T 12811-2025 "Test Method for Average Cell Size of Rigid Foamed Plastics".
[0108] The test method for closed cell rate was determined by using the national standard GB / T 10799-2008 "Determination of Open and Closed Cell Volume Fractions of Rigid Foamed Plastics".
[0109] The test method for strength retention rate after 100 times of temperature cycle was as follows: first, test the initial 25% compression strength; then, repeat 100 times of a cycle of constant temperature treatment at -30°C for 2 hours and constant temperature treatment at 70°C for 2 hours; finally, test the 25% compression strength after the cycle, and then calculate the strength retention rate after 100 times of temperature cycle by the following formula: strength retention rate after 100 times of temperature cycle = (25% compression strength after the cycle / initial 25% compression strength) x 100%.
[0110] The test method for the thermal conductivity after 5 years of aging is as follows: first, the initial thermal conductivity is measured according to the national standard GB / T 10294-200; then, the accelerated aging is carried out according to the national standard GB / T 20219-2006 "Hard Foam Plastic Accelerated Aging Test Method" under the condition of 70℃±2℃ and relative humidity of 65%±5% until the corresponding time length of 5 years of natural aging; finally, the thermal conductivity after aging is measured according to the national standard GB / T 10294-2008.
[0111] The relative values of raw material costs in Table 3 and Table 4 refer to: the calculation basis of the relative values of raw material costs is the cost of the polyurethane foam composition of Comparative Example 6 (set as 1), and the relative values of the costs of the polyurethane foam compositions of Examples 1-3 and Comparative Examples 1-5 are the ratios of the respective costs to the cost of Comparative Example 6.
[0112] Table 3:
[0113] Table 4:
[0114] In the brackets of each performance parameter in Table 3 and Table 4, ↓ represents decrease, and ↑ represents increase, both of which are the increase or decrease relative to the corresponding value of Example 1. For example, (↑23.5%) in the thermal conductivity of Comparative Example 1 means that the thermal conductivity of the polyurethane foam of Comparative Example 1 is increased by 23.5% compared with the thermal conductivity of the polyurethane foam of Example 1; (↓31.6%) in the 25% compression strength of Comparative Example 1 means that the 25% compression strength of the polyurethane foam of Comparative Example 1 is decreased by 31.6% compared with the 25% compression strength of the polyurethane foam of Example 1.
[0115] From Table 3 and Table 4, it can be seen that: Compared with the polyurethane foams of Comparative Examples 1-5, the polyurethane foams of Examples 1-3 have lower thermal conductivity, higher compressive strength, smaller cell diameter, higher closed cell rate, smaller performance fluctuation, higher strength retention rate, and lower thermal conductivity after 5 years of aging (i.e., higher thermal conductivity stability). It can be seen that the polyurethane foams prepared from the polyurethane foam composition described in the present application have lower thermal conductivity, higher compressive strength, smaller cell diameter, higher closed cell rate, smaller performance fluctuation, higher strength retention rate, and lower thermal conductivity after 5 years of aging. The reason may be that the polyurethane foam composition described in the present application can effectively reduce the thermal conductivity of the polyurethane foam prepared therefrom through the synergistic effect between the components and their contents. It can also solve the problem of interfacial compatibility between the high-load filler and the foam matrix of the polyurethane foam, effectively improve the compressive strength of the polyurethane foam, and have higher compressive strength stability. The polyurethane foam composition is suitable for a high filler system and is beneficial to making the cell size of the prepared polyurethane foam have higher uniformity. In addition, the preparation method of the polyurethane foam described in the present application uses the polyurethane foam composition described above as raw material, and utilizes the ternary synergistic effect of “high-load double-modified filler (modified hollow glass microsphere and modified nano-silicon dioxide) + low-GWP blowing agent + gradient pressure foaming process”, which can effectively improve the interfacial compatibility between the filler and the foam matrix, and also make the cells in the polyurethane foam have higher uniformity. It achieves the synergistic balance of “mechanical enhancement effect of high-load filler + low thermal conductivity effect of LBA + cell uniformization effect of gradient pressure reduction foaming process”, effectively reduces the thermal conductivity of the polyurethane foam, and breaks through the thermal conductivity bottleneck of the existing blowing agent and filler system.
[0116] Compared with the polyurethane foams of Comparative Examples 1 and 3, in the polyurethane foams of Examples 1-3, the HGM is deeply grafted with amino groups by KH550 (grafting rate ≥ 1.8%), and the modified HGM has higher bonding strength with the -NCO bond of the polyurethane. The nano-SiO2 is pretreated with KH560 to form a double hydrogen bond with the polyol, and a “strong bonding + high adsorption” double interface structure is constructed, which is suitable for high filler loading. In this way, the interfacial bonding strength between the filler and the foam matrix in the polyurethane foam of Example 1 is increased by 60% compared with Comparative Examples 1 and 3, and the 25% compressive strength is ≥ 0.35 MPa, which can effectively solve the problem of “interfacial shedding leading to sudden increase in thermal conductivity” under high filler loading.
[0117] Compared with the polyurethane foam of Comparative Example 2, in the polyurethane foams of Examples 1-3, the blowing agent provides a low-thermal-conductivity gas-phase environment (gas-phase thermal conductivity ≤ 0.012 W / (m K) ), high-load HGM blocks long-distance solid-phase heat conduction, and superfine nano-SiO2 refines the cell size to 80-150 μm, forming a "solid-gas-superfine cell" triple high-efficiency heat insulation barrier. Thus, the thermal conductivity can be reduced to 0.017 W / (m K) below, and the thermal conductivity increases by ≤3% after 5 years of aging.
[0118] Compared with the polyurethane foam of Comparative Example 4, in the polyurethane foams of Examples 1-3, through the cooperation of "high-pressure nucleation (nucleation at the first gas pressure) + low-pressure growth (growth at the second gas pressure)" and "precise gradient temperature control of 48-58°C", the high filler dispersion and the superfine cell growth rate can be effectively balanced. Thus, the cell size uniformity is effectively improved, the performance fluctuation is ≤2%, and the batch production stability of the high filler system is effectively solved.
[0119] The polyurethane foams of Example 1 and Comparative Example 1 are respectively used in a 600L household side-by-side refrigerator. Compared with the polyurethane foam of Comparative Example 1, the polyurethane foam of Example 1 can reduce the insulation layer thickness from 80mm to 50mm, increase the refrigerator volume by 8%, and reduce the energy consumption from 0.8kWh / 24h to 0.4kWh / 24h, which exceeds the 1st level energy efficiency standard of GB 12021.2-2015.
[0120] The polyurethane foams of Example 1 and Comparative Example 1 are respectively used in a 1000L vertical commercial low-temperature display cabinet (-25°C). Compared with the polyurethane foam of Comparative Example 1, the polyurethane foam of Example 1 can reduce the cold damage rate from 15% to 5%, and the daily average power consumption from 5.0kWh to 2.8kWh, and the polyurethane foam of Example 1 has no cracking at -30°C low temperature.
[0121] The polyurethane foams of Example 1 and Comparative Example 1 are respectively used in a drawer insulation layer. Compared with the polyurethane foam of Comparative Example 1, the polyurethane foam of Example 1 has a weight reduction of 18%, and has no deformation (dimensional change rate ≤0.5%) when accelerated aging at 70°C±2°C and relative humidity 65%±5% to the corresponding 5-year natural aging time.
[0122] The above describes the technical solutions provided by the embodiments of the present application in detail. The specific examples are applied to explain the principles and implementation modes of the present application. The above examples are only used to help understand the method and core idea of the present application; meanwhile, for those skilled in the art, the specific implementation modes and application ranges can be changed according to the idea of the present application. In summary, the content of the specification should not be understood as a limitation of the present application.
Claims
1. A polyurethane foam composition characterized in that, The polyurethane foam composition comprises component A and component B, the component A comprises polyol, blowing agent, modified hollow glass microsphere, modified nanosilica and additive, the additive comprises one or more of catalyst, stabilizer and antioxidant, the component B comprises isocyanate, wherein, The content of the polyol is 28-35 parts by mass, the content of the blowing agent is 12-18 parts by mass, the content of the modified hollow glass microsphere is 8-15 parts by mass, the content of the modified nanosilica is 6-10 parts by mass, the content of the catalyst is 0.5-0.9 parts by mass, the content of the stabilizer is 1.2-1.6 parts by mass, the content of the antioxidant is 0.5-0.7 parts by mass, and the content of the isocyanate is 38-45 parts by mass.
2. The polyurethane foam composition of claim 1, wherein The modified hollow glass microsphere comprises silane coupling agent grafted modified hollow glass microsphere, and the silane coupling agent grafted modified hollow glass microsphere comprises hollow glass microsphere and first silane coupling agent on the surface of the hollow glass microsphere; And / or, the modified nanosilica comprises silane coupling agent grafted modified nanosilica, and the silane coupling agent grafted modified nanosilica comprises nanosilica and second silane coupling agent on the surface of the nanosilica.
3. The polyurethane foam composition of claim 2, wherein The average particle size of the hollow glass microsphere is 50-80 µm; and / or the hollow glass microspheres have a D 50 of 55-75 pm; And / or, the average particle size of the nanosilica is 15-25 nm; and / or the D50 of the nanosilica is from 5 to 25 nm. 50 from 5 to 25 nm. and / or the D50 of the nanosilica is from 80 to 250 nm; and / or the D50 of the nanosilica is from 80 to 250 nm. 90 from 80 to 250 nm. And / or, the grafting rate of the silane coupling agent in the silane coupling agent grafted modified hollow glass microsphere is 1.8wt%-12wt%; And / or, the grafting rate of the silane coupling agent in the silane coupling agent grafted modified nanosilica is 2wt%-15wt%; The first silane coupling agent and the second silane coupling agent each independently comprise one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, ureidopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, bis(3-trimethoxysilylpropyl)amine, γ-mercaptopropyltriethoxysilane, vinyltriethoxysilane, and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane.
4. The polyurethane foam composition of claim 1, wherein, The polyol comprises polyether polyol, wherein The hydroxyl value of the polyether polyol is 51-61 mgKOH / g; And / or, the polyether polyol comprises long-chain polyether alcohol, the molecular weight of the long-chain polyether alcohol is 2000-5000, and the long-chain polyether alcohol comprises polypropylene glycol.
5. The polyurethane foam composition of claim 1, wherein The isocyanate includes polymeric diphenylmethane diisocyanate, the functionality of the polymeric diphenylmethane diisocyanate is 2.6~3.0, the viscosity of the polymeric diphenylmethane diisocyanate is 150~210 mPa S, in the polymeric diphenylmethane diisocyanate, the content of -NCO is 30~32wt%; And / or, the catalyst comprises one or more of an amine catalyst and an organic metal compound catalyst, the amine catalyst comprises one or more of triethylenediamine, dibutyltin dilaurate, N,N-dimethylcyclohexylamine, N,N,N',N'-tetramethylethylenediamine, dimethylethanolamine, N,N-dimethylbenzylamine, 2,2'-dimorpholinodiethylether, the organic metal compound catalyst comprises one or more of zinc octoate, bismuth iso-octoate, tetrabutyl titanate, lead naphthenate; And / or, the stabilizer comprises a silicone oil, the silicone oil has a viscosity of 200-300 mPa s at 25°C, a surface tension of 18-23 mN / m, and the silicone oil comprises one or more of the following: Moment L-6900 silicone oil, Moment L-7001 silicone oil, Moment L-580 silicone oil, Moment L-620 silicone oil, Dow Corning DC-193 silicone oil, Dow Corning DC-5043 silicone oil, Dow Corning DC-198 silicone oil, Suzhou Sider SD-613 silicone oil, Suzhou Sider SD-624 silicone oil, BYK-346 silicone oil, Dema FM-9901 silicone oil, Wacker AK-8803 silicone oil, Wacker AK-8815 silicone oil, fluorine-containing modified silicone oil, and one or more of the following: hydroxyl-terminated fluorosilicone oil, fluorine-containing polyglyceryl ether-polydimethylsiloxane block copolymer. And / or, the foaming agent comprises one or more of a physical foaming agent and a chemical foaming agent, the physical foaming agent comprises one or more of a hydrocarbon physical foaming agent, a fluoroalkene foaming agent, an ester foaming agent, an alcohol ether foaming agent, a bio-based foaming agent, a supercritical fluid foaming agent, wherein the hydrocarbon physical foaming agent comprises one or more of cyclopentane, isopentane, n-pentane, cyclohexane, the fluoroalkene foaming agent comprises one or more of 1-chloro-3,3,3-trifluoropropene foaming agent, 2,3,3,3-tetrafluoropropene foaming agent, 1,3,3,3-tetrafluoropropene foaming agent, the ester foaming agent comprises one or more of ethyl acetate, dimethyl carbonate, the alcohol ether foaming agent comprises one or more of dimethyl ether, methoxy ethanol, the bio-based foaming agent comprises one or more of limonene derivatives, turpentine-based compounds, the supercritical fluid foaming agent comprises supercritical CO2, the chemical foaming agent comprises one or more of water, formic acid, oxalic acid; And / or, the antioxidant comprises one or more of a hindered phenol antioxidant, a phosphite antioxidant, a thioester antioxidant, an amine antioxidant, the hindered phenol antioxidant comprises one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionates octadecyl alcohol, N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, triethylene glycol bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, the phosphite antioxidant comprises one or more of tris[2.4-di-tert-butylphenyl]phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, the thioester antioxidant comprises one or more of dilauryl thiodipropionate, distearyl thiodipropionate, the amine antioxidant comprises one or more of N-isopropyl-N'-phenyl-p-phenylenediamine, N,N'-bis(β-naphthyl)-p-phenylenediamine.
6. A process for the preparation of a polyurethane foam, characterized in that, Comprising the following steps: Providing the polyurethane foam composition according to any one of claims 1-5, mixing component A and component B in the polyurethane foam composition, foaming under pressure at a first gas pressure; Reducing the pressure to a second gas pressure, foaming under pressure at the second gas pressure, to obtain a polyurethane foam.
7. The preparation method of claim 6, wherein, The first air pressure is 1-1.2 Mpa; And / or, the second air pressure is 0.2-0.4 Mpa; And / or, the decompression rate to the second air pressure is 0.1-0.14 MPa / min; And / or, the time of pressure foaming at the first air pressure is 55-65 seconds; And / or, the time of pressure foaming at the second air pressure is 2.7-3.3 min; And / or, the temperature of pressure foaming at the first air pressure is 46-50℃; And / or, the temperature of pressure foaming at the second air pressure is 56-60℃; And / or, the air pressure of mixing component A and component B in the polyurethane foam composition is 16-20 Mpa.
8. The production method according to claim 6, wherein After pressure foaming at the second air pressure and before obtaining the polyurethane foam, further comprising: sequentially performing a first heat curing treatment and a second heat curing treatment, the temperature of the first heat curing treatment is lower than the temperature of the second heat curing treatment, wherein, The temperature of the first heat curing treatment is 68-72℃, and the time of the first heat curing treatment is 13-17 h; And / or, the temperature of the second heat curing treatment is 72-77℃, and the time of the second heat curing treatment is 26-30 h.
9. The production method according to claim 6, wherein The preparation of the component A comprises the following steps: Mixing the hollow glass microsphere dispersion liquid with the first silane coupling agent, the hollow glass microsphere dispersion liquid comprising hollow glass microspheres, first heat treatment, grafting the first silane coupling agent to the surface of the hollow glass microspheres to obtain modified hollow glass microspheres; Mixing the nano-silica dispersion liquid with the second silane coupling agent, the nano-silica dispersion liquid comprising nano-silica, second heat treatment, grafting the second silane coupling agent to the surface of the nano-silica to obtain modified nano-silica; Mixing the modified hollow glass microspheres, the modified nano-silica, polyol and additives to obtain a mixed liquid; Mixing the mixed liquid with a foaming agent to obtain component A.
10. The preparation method of claim 9, wherein, The temperature of the first heat treatment and the temperature of the second heat treatment are each independently 70-80℃; And / or, the time of the first heat treatment and the time of the second heat treatment are each independently 2-3 h; And / or, the temperature of mixing the modified hollow glass microspheres, the modified nano-silica and additives is 20-24℃; And / or, the first silane coupling agent accounts for 2-15% of the mass of the hollow glass microspheres; And / or, the second silane coupling agent accounts for 2-20% of the mass of the nano-silica.
11. A polyurethane foam characterized by, The polyurethane foam composition of any one of claims 1-5 after foaming, or prepared by the preparation method of any one of claims 6-10.
12. The polyurethane foam according to claim 11, wherein, The polyurethane foam comprises a foam matrix and a filler dispersed in the foam matrix, the filler comprising modified hollow glass microspheres and modified nano-silica, and the material of the foam matrix comprising polyurethane.
13. The polyurethane foam of claim 12, wherein, The closed cell rate of the polyurethane foam is greater than or equal to 97%. And / or, the pore size of the cells in the polyurethane foam is 80-150 μm; And / or, the weight average polymerization degree of the polyurethane is 3000-6000; and / or the polyurethane foam has a thermal conductivity of less than or equal to 0.017 W / (m K). And / or, in the polyurethane foam, the content of the polyurethane is 50wt%-70wt%, the content of the modified hollow glass microsphere is 20wt%-35wt%, and the content of the modified nanosilica is 5wt%-15wt%.
14. A refrigeration apparatus characterized by comprising: The polyurethane foam according to any one of claims 11-13.
Citation Information
Cited By
Multifunctional polyurethane foaming material for building materials and preparation process thereof
CN121779672A
Multifunctional polyurethane foam for building materials and process for its preparation
CN121779672B